2018
DOI: 10.1111/tbj.13041
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of recurrence patterns and survival in modern series of young women with breast cancer

Abstract: The data on oncologic outcomes in young women with breast cancer (BC) are dated as it relates to recurrences and mortality. Our goal was to assess these outcomes in a modern series of young women with BC. A retrospective chart review identified women ≤40 years old with stage I-III BC diagnosed from 2006 to 2013 at our institution. Demographics, tumor biology, type of operation, recurrence, and survival were analyzed. Overall, 322 women were identified. Most had ER+(70%) infiltrating ductal tumors (88%) with lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…It does appear that conflicting results regarding the role of tumor biology, including tumor grade, ER, PR, and HER2 status in young breast cancer. Several prior studies showed similar or inferior outcomes related to ER positive status in young patients [21][22][23][24][25][26][27], while others demonstrated superior outcomes associated with ER positive status [28,29]. It was hypothesized that young patients have lower compliance with hormonal therapy [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It does appear that conflicting results regarding the role of tumor biology, including tumor grade, ER, PR, and HER2 status in young breast cancer. Several prior studies showed similar or inferior outcomes related to ER positive status in young patients [21][22][23][24][25][26][27], while others demonstrated superior outcomes associated with ER positive status [28,29]. It was hypothesized that young patients have lower compliance with hormonal therapy [34].…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have validated the prognostic effect of the new staging system in breast cancer [18][19][20]. However, the prognostic impact of tumor biologic factors incorporated in the current staging system of young patients remains controversial [21][22][23][24][25][26][27][28][29][30][31][32][33]. Several prior studies showed similar or inferior outcomes related to ER-positive status in young women [21][22][23][24][25][26][27], while others indicated better survival rates associated with ER-positive status [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…This necessitates early detection and prompt treatment of these young patients, as the delay in management may have a huge impact on their survival. 11 Also, this can be of interest in upcoming studies. To gain a better understanding of the behavior of breast cancer in young women, we analyzed the pathological and biological features of the disease.…”
Section: Discussionmentioning
confidence: 96%